I codici bruciati della Biblioteca Nazionale Universitaria di Torino: le problematiche del restauro - Cachia, Véronique (Scrineum, 2020)
The parchment codices of the National Library of Turin, heavily destroyed by fire in 1904, had very complex damages due to the thermal contraction of the writing support. The covers were burnt so the leaves got mixed up, some were stuck together because of the deteriora- tion of collagen. In some cases they formed very hard blocks. In 2000 the National Library of Turin started a project to complete the restoration of the entire manuscripts collection, in cooperation with the Università degli Sudi of Turin, the Politecnico of Milan and the Istituto Cen- trale per la Patologia del Libro of Rome. The experimentation was based on sophisticated analysis on old, new, fire-damaged and non-damaged samples, in order to find a restoring process that would be able to give back flexibility to parchment, to separate the agglutinated pages and to flatten them. The process was composed in different phases: preliminary interven- tions, wet treatments and flattening. Some pigments and inks were found out to be soluble during the wet treatments, so part of the testing had been focused on the identification of an efficient fixative that would not alterate the colour of the pigment. This experimentation has allowed us to write down a protocol for the restoration of fire-damaged parchment.